Analysis on Employee Job Satisfaction at Daluman Villa - Sekarini Sekarini; I Ketut Surata; Desak Gede Chandra Widayanthi; I Wayan Restu Darmawan (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
Employee satisfaction level is important to be maintained at the workplace to make them performed well at the workplace. This research focuses on the level of satisfaction at Daluman Villa. The level of employee satisfaction was analyzed using Gruneberg theory as the fundamental theory in constructing this research. The data obtained were collected from the questionnaire distribution and interview. The questionnaire data obtained were tested its validity and reliability using SPSS system and Cronbach’s Alpha. The data obtained were discussed by using descriptive analysis and qualitative analysis. The result from the research is most employees are satisfied with the indicators stated by Gruneberg theory. To Daluman Villa, it could be suggested that they should maintaining the good practices that have been done in order to keep the employees satisfied with their job, thus their performance and productivity would be maintained as well, or even enhanced.